MicroRNA‐142 is a multifaceted regulator in organogenesis, homeostasis, and disease - Amit Shrestha; Regina Mukhametshina; Sara Taghizadeh; Esmeralda Vásquez‐Pacheco; Hector A. Cabrera‐Fuentes; Albert A. Rizvanov; Bernard Mari; Gianni Carraro; Savério Bellusci (2016)
Over the past decade, microRNA-142 (miR-142) is emerging as a major regulator of cell fate decision in the hematopoietic system. However, miR-142 is expressed in many other tissues, and recent evidence suggests that it may play a more pleiotropic role during embryonic development. In addition, miR-142 has been shown to play important functions in disease. miR-142 displays a functional role in cancer, virus infection, inflammation, and immune tolerance. Both a guide strand (miR-142-3p) and passenger strand (miR-142-5p) are generated from the miR-142 hairpin. miR-142-3p and -5p display overlapping but also independent target genes. Loss of function mouse models (genetrap, global knock out [KO], and conditional KO) have been reported and support the important role of miR-142 in different biological processes. This review will summarize the abundant literature already available for miR-142 and will lay the foundation for future works on this important microRNA. Developmental Dynamics 246:285-290, 2017. © 2016 Wiley Periodicals, Inc.